2004
DOI: 10.1007/s00424-004-1340-z
|View full text |Cite
|
Sign up to set email alerts
|

High glucose concentrations stimulate human monocyte sodium/hydrogen exchanger activity and modulate atherosclerosis-related functions

Abstract: In the present study, the effect of high (20 mM) glucose concentrations on human monocyte sodium/hydrogen exchanger (NHE1) activity, scavenger receptor CD36 expression, cell adhesion, and cell migration have been investigated. Incubation with high glucose concentrations caused an increase in NHE1 activity, as estimated by internal pH and sodium-uptake measurements. This effect was specific for glucose, since it was not observed when monocytes were incubated in the presence of 20 mM of galactose, fructose, or m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
20
0
6

Year Published

2005
2005
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(31 citation statements)
references
References 39 publications
5
20
0
6
Order By: Relevance
“…In our study, it has been detected that glucose can influence the de novo synthesis of non-glycated CD36 proteins, which appeared sooner and in higher levels when the glucose concentration was higher; this effect, however, seemed to be limited by time. Higher glucose concentration also inhibited glycated CD36 expression in healthy subjects, as has been reported [27], though other authors have found contrary results [23, 25]. Inhibition was shown since the beginning of the study and was not as important in monocytes cultured in lower glucose levels (EG conditions), which later showed a decrease in glycated CD36 protein expression.…”
Section: Discussionsupporting
confidence: 68%
“…In our study, it has been detected that glucose can influence the de novo synthesis of non-glycated CD36 proteins, which appeared sooner and in higher levels when the glucose concentration was higher; this effect, however, seemed to be limited by time. Higher glucose concentration also inhibited glycated CD36 expression in healthy subjects, as has been reported [27], though other authors have found contrary results [23, 25]. Inhibition was shown since the beginning of the study and was not as important in monocytes cultured in lower glucose levels (EG conditions), which later showed a decrease in glycated CD36 protein expression.…”
Section: Discussionsupporting
confidence: 68%
“…This ubiquitously expressed isoform has a major housekeeping role through the regulation of intracellular pH (pHi) and cell volume via the exchange of extracellular Na + with H + in a 1:1 ratio (Putney et al 2002). Additionally, through its cytoplasmic C-terminal domains, NHE1 is known to interact with the cytoskeleton as well as a variety of cytoplasmic proteins, through which it accepts signals initiated by molecules such as glucose, hormones, and others which affect its activation (Bourikas et al 2003;Koliakos et al 2004). Through these interactions, NHE1 is both itself regulated and also able to regulate cellular functions such as cell motility and cell survival (Malo and Fliegel 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Transmigration of monocytes through laminin-1-coated filters was performed as previously described [18]. In brief, filters of 6.5 mm diameter, 5-µm pore Transwell culture inserts (Costar, Cambridge, Mass., USA) were coated with 20-µg/ml laminin-1 and left to dry overnight at 4°C.…”
Section: Methodsmentioning
confidence: 99%